Exploring potential climate-related entrepreneurship opportunities and challenges for rural Nigerian women - C. A. O. Akinbami; J. E. Olawoye; F. A. Adesina; Valerie Nelson (Journal of Global Entrepreneurship Research, 2019)
Entrepreneurship is a tool for facilitating rural economic development, which is becoming increasingly needed to respond to the growing impacts of accelerating climate change on rural women's livelihoods in less developed countries creating constraints on sustainable development. This study examines the awareness of and impacts of climatic changes as perceived by women in South West Nigeria in diverse vegetation zones. It elicits the challenges facing women and which constrain their entrepreneurial activities. It therefore identifies potential adaptation strategies and opportunities, including drawing on a review of wider developments in at international development level, such as technological, institutional and infrastructural innovations. The study employed explorative, mixed approaches, including quantitative and qualitative methods. Five hundred and ninety-five questionnaires were administered to selected respondents through multi-stage sampling technique, while Focused Group Discussions (FGDs) were used to solicit qualitative data from two hundred and forty women. Quantitative data were analysed with SPSS for descriptive and analysis of variance, and Atlas ti. was used to thematically analyse qualitative data. Findings showed that women have high levels of awareness of changes in their climate. Analysis of variance revealed that most of the women involved in crop farming in the vegetation zones showed better understanding than women in other livelihood. They strongly agreed (with mean of approximately 5) that climate change had greatly affected soil fertility, caused less predictable, and prolonged the dry season. Over 90% of the women perceived significant impacts of these changes on their livelihood activities. Overall, there were no clear divergences in women's attitudes towards innovation and entrepreneurship between the vegetation zones and a relatively high expectation of government support. Wider review of current practice and innovations highlights a wide range of new opportunities for building women's adaptive capacity which could directly or indirectly catalyse increased entrepreneurship amongst women. Furthermore, the involvement of local authorities and community-based organisations, as well as diverse public and private actors, in the development of adaptation strategies is crucial to achieving this.
Keywords: 650; Entrepreneurship; Climate change; Adaptation strategies; Rural women; Challenges; Opportunities